Assessing the Economic Benefits of Higher Education - Baltar, Christia C. (JPAIR Institutional Research, 2018)
The Philippines produces more than 1.5 million high school graduates and approximately 500,000 students who proceeded and graduated in college every year. The economic benefits of having a degree may attract students to pursue tertiary education. The researcher wanted to determine the economic benefit of higher education. Secondary data from various government agencies were gathered and utilized in this study. A survey to 90 graduates of secondary education and 98 graduates of higher education was done using purposive sampling. The descriptive measures, chi-square test, and the correlation coefficient were employed for the analyses. Enrolling in higher education is quite difficult for some families who can’t afford tertiary education which is influenced by three components; the government budget for education, the proportion of income spent for education, and employability. Findings clearly stated that there is a high income when you are a graduate of higher education. The sex, age, and marital status do not have a significant relationship to the earnings of the graduates; however, the bachelors’ degree is significantly related. Finally, the researcher concludes that attaining higher education can be seen directly to the increased earnings. The researcher recommends looking into other factors which affect the household income and its relationship to the attainment of tertiary education.